Growth factor cocktail to facilitate epithelial differentiation of exfoliated deciduous teeth stem cells - Nurul Hafizah Mohd Nor,; Zurairah Berahim,; Azlina Ahmad,; Thirumulu Ponnuraj Kannan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Epithelial cells are important in the regeneration of oral mucosal tissue. The cell source is commonly derived from tissue biopsy, which is obtained through surgery. Stem cells from human exfoliated deciduous teeth (SHED) were demonstrated to differentiate into multiple cell types. As it can be readily available from exfoliated deciduous teeth, it can be induced and become a potential source of epithelial cell for oral tissue study. This study aims to examine a mixture of growth factors in the differentiation of epithelial-like cells obtained from human exfoliated deciduous teeth (SHED) stem cells. This growth factor cocktail constitutes hepatocyte growth factor (HGF), keratinocyte growth factor (KGF), insulin-like growth factor 2 (IGF-II), and epidermal growth factor (EGF). After introducing the cocktail, the treated SHED were assessed for epithelial characteristics and markers using cell proliferation test, morphological transformation, protein and gene expression by immunofluorescence staining and cytometry assessment, respectively. The proliferation rate was analysed statistically using Analysis of Variance (ANOVA) with Repeated Measures (p<0.05). SHED cells demonstrated morphological changes on the 7th day after using the cocktail. These transformations are in alignment with the identification of genes associated with epithelial cells and positive stain outcomes for pan-cytokeratin, E-cadherin, and p63. The cell proliferation test indicated that proliferation of cells and growth factor introduction were significantly correlated. The growth factor cocktail used for this research facilitated SHED differentiation for epithelial-like cells. The outcomes validate the production of epithelial cells using SHED; tissue production studies focus on these aspects immensely.